2022
DOI: 10.1002/osp4.645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the built, social, and food environment on long‐term weight loss within a behavioral weight loss intervention

Abstract: Background Behavioral weight loss interventions can lead to an average weight loss of 5%–10% of initial body weight, however there is wide individual variability in treatment response. Although built, social, and community food environments can have potential direct and indirect influences on body weight (through their influence on physical activity and energy intake), these environmental factors are rarely considered as predictors of variation in weight loss. Objective Evaluate the association between built, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Managing type 2 diabetes, including taking medicines, maintaining a healthy lifestyle, and monitoring blood glucose levels can be stressful, and this can be a factor in the development of depression and thoughts of suicide. Furthermore, the combination of type 2 diabetes and depression may be particularly evident in deprived socio-economic groups, possibly due to food insecurity issues [1,[86][87][88][89]. Based on the content of current posts, these inequalities were possibly behind those posts reporting difficulties in both getting a prescription and communicating with physicians, which, in turn, may be due to healthcare access and health insurance issues.…”
Section: Discussionmentioning
confidence: 99%
“…Managing type 2 diabetes, including taking medicines, maintaining a healthy lifestyle, and monitoring blood glucose levels can be stressful, and this can be a factor in the development of depression and thoughts of suicide. Furthermore, the combination of type 2 diabetes and depression may be particularly evident in deprived socio-economic groups, possibly due to food insecurity issues [1,[86][87][88][89]. Based on the content of current posts, these inequalities were possibly behind those posts reporting difficulties in both getting a prescription and communicating with physicians, which, in turn, may be due to healthcare access and health insurance issues.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, limited evidence suggests there is an increased consumption of fresh fruit and vegetables when access is increased [75]. Not only is the built environment related to obesity risk and physical activity, but data support that environmental factors, including grocery store density, walkability, and economic status of a neighborhood, explains up to 11% of the variability in response to a weight-loss intervention [79]. It is likely that such factors are also involved in the success of WLM.…”
Section: The Built Environmentmentioning
confidence: 99%
“…Cooking intervention studies including African Americans have reported improvement in self-reported dietary quality, but the overall inclusion of African Americans within clinical nutrition interventions remains a key gap area for addressing diet-related disease disparities [11]. Community-tailored cooking interventions may be required for the necessary inclusion of African Americans within intervention studies as African Americans represent racially categorized individuals who disproportionately live within racialized communities that serve as impediments to dietary quality as a result of adverse environmental and social factors [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%